Association between childhood anthropometric indicators and bone mineral density in adulthood - Mileny Caroline Menezes de Freitas; Julio Cesar da Costa; Cynthia Correa Lopes Barbosa; Lidyane Ferreira Zambrin; Catiana Leila Possamai Romanzini; Marcelo Romanzini; Enio Ricardo Vaz Ronque (Sociedade de Pediatria de São Paulo, 2023)
ABSTRACT Objective: This study aimed to verify the association between childhood anthropometric indicators and areal bone mineral density (aBMD) in adulthood. Methods: Repeated measures of 137 subjects (68 females) were obtained in childhood (9.2±1.5 years of age) and adulthood (22.3±1.7 years of age). aBMD (g/cm2) was assessed for whole body, lumbar spine, upper and lower limbs, and femoral neck in adulthood using dual-energy X-ray absorptiometry. Anthropometric measurements of body weight (BW), height, triceps and subscapular skinfolds were obtained in childhood. The anthropometric indicators used were BW, body mass index (BMI), and sum of skinfolds (ΣSF). Simple linear regression was used to assess the association between childhood anthropometric indicators and aBMD in adulthood, controlled by chronological age and stratified by sex, with 5% statistical significance. Results: In females, multiple associations were observed between anthropometric indicators and aBMD, with higher coefficients for BMI (β=0.020; R2=0.20; p<0.01 for right femoral neck to β=0.008; R2=0.16; p<0.01 for upper limbs), followed by BW (β=0.003; R2=0.21; p<0.01 for upper limbs to β=0.008; R2=0.20; p<0.01 for right femoral neck) and ΣSF (β=0.001; R2=0.06; p<0.01 for upper limbs to β=0.005; R2=0.12; p<0.01 for right femoral neck). In males, associations were observed only for the lumbar spine region (β=0.016; R2=0.09 for BMI to β=0.004; R2=0.06; p<0.01 for ΣSF). Conclusions: Anthropometric indicators of childhood proved to be sensitive predictors of aBMD in adulthood, especially in females. BMI indicated a greater association with aBMD in both sexes.